Strategi Komunikasi BKKBN Dalam Upaya Menurunkan Kasus Stunting di Kabupaten Banyuasin Provinsi Sumatera Selatan (Studi Kasus Kenaikan Kasus Stunting di Kabupaten Banyuasin Pada Tahun 2022) - Mutia Anindri; Susanne Dida; Hanny Hafiar (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Stunting can be said to be a threat to the quality of human resources in Indonesia, besides that stunting can also be a menace to inter-national competitiveness, because the child affected by stunting is not only disturbed by his physical growth but also disrupted by his brain growth or slowed development of cognitive or intellectual, motoric, and verbal. So this study aims to know how the communication strategy carried out by BKKBN district Banyuasin in implementing the stunting reduction program of how its planning, implementation and evaluation, as well as to know the causes of the occurrence of the rise of stunting cases in the district banyuasin by 2022 in particular in the area of its communication strategy in the study of health communication. The result was stunting due to poor performance of stunting management secretariat and increased early marriage age in Banyuasin district, in addition to the birth distance is very close and still many mothers refuse to use KB. However, BKKBN has already taken action by providing education and assistance in the form of milk, and supplementary food for babies and young children, as well as giving vaccines to the whole catin and providing nutritional supplements for pregnant mothers. In addition to providing additional food, milk and also vaccine assistance. So from that, the theory of social construction over reality in particular Social reality Objectives such as brochures, posters, and videos, to disseminate information about the importance of balanced nutrition and sufficient intake of vitamins and minerals for normal physical growth to avoid stunting can help the community of Banyuasin district in understanding the social construction of stunting.